Revealing Tactical Intelligence: A Phenomenological Exploration of Gender Based Decision Making in Volleyball - Mohamad Rizki Muhaimin; Tatang Muhtar; Muhammad Nur Alif (Tadulako Journal Sport Sciences And Physical Education, 2026)
The purpose of this study was to test the tactical ability of male and female volleyball athletes to play based on their direct experience during training and competition. A qualitative approach with phenomenological design is used to explore the interpretation of athletes about reading the game, decision making, communication, and strategic adjustment in the match situation. There were eight participants consisting of four male athletes and four female athletes who were taken using purposive sampling technique. Selection criteria include active participation in training, minimum of three years playing experience, involvement in official competitions and willingness to be research informants. NVivo was used for data analysis, including data reduction, data display and conclusion drawing on the data gathered from semi-structured interviews, observation and documentation. The results indicated that tactical skills were affected by decision making, game reading, psychological factors, team communication, basic technique mastery, position, guarding, ball anticipation, training experience, and characteristics of playing by gender. Male athletes in terms of game character have a faster, stronger and more explosive game, while female athletes tend to play slower with longer rallies. The second group was influenced by technical and situational factors in decision making aspects. The study concluded that the tactical capabilities should be developed through an integrated training program covering technical, situational, mental, communicative and gender responsive aspects to optimize volleyball performance.